Cytotoxicity of glucoevatromonoside alone and in combination with chemotherapy drugs and their effects on Na+,K+-ATPase and ion channels on lung cancer cells - Zanchett Schneider, Naira Fernanda; Menegaz, Danusa; Andreotti Dagostin, Andre Luiz; Persich, Lara; Rocha, Sayonarah C.; Pacheco Ramos, Ana Carolina; Cortes, Vanessa Faria; Leite Fontes, Carlos Frederico; De Padua, Rodrigo Maia; Munkert, Jennifer; Kreis, Wolfgang; Braga, Fernao Castro; et al. (Molecular and Cellular Biochemistry, 2021)
Cardiac glycosides (CGs) are useful drugs to treat cardiac illnesses and have potent cytotoxic and anticancer effects in cultured cells and animal models. Their receptor is the Na+,K+ ATPase, but other plasma membrane proteins might bind CGs as well. Herein, we evaluated the short- and long-lasting cytotoxic effects of the natural cardenolide glucoevatromonoside (GEV) on non-small-cell lung cancer H460 cells. We also tested GEV effects on Na+,K+ -ATPase activity and membrane currents, alone or in combination with selected chemotherapy drugs. GEV reduced viability, migration, and invasion of H460 cells spheroids. It also induced cell cycle arrest and death and reduced the clonogenic survival and cumulative population doubling. GEV inhibited Na+,K+-ATPase activity on A549 and H460 cells and purified pig kidney cells membrane. However, it showed no activity on the human red blood cell plasma membrane. Additionally, GEV triggered a Cl-mediated conductance on H460 cells without affecting the transient voltage-gated sodium current. The administration of GEV in combination with the chemotherapeutic drugs paclitaxel (PAC), cisplatin (CIS), irinotecan (IRI), and etoposide (ETO) showed synergistic antiproliferative effects, especially when combined with GEV + CIS and GEV + PAC. Taken together, our results demonstrate that GEV is a potential drug for cancer therapy because it reduces lung cancer H460 cell viability, migration, and invasion. Our results also reveal a link between the Na+,K+-ATPase and Cl- ion channels.
CRIS-Team WoS Importer:2021-02-12